2017
DOI: 10.1016/j.aott.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of the fixation systems for anterior column and posterior hemi-transverse acetabular fractures

Abstract: ObjectiveThe aim of this study was to evaluate the biomechanical properties of common fixation systems for complex acetabular fractures.MethodsA finite element (FE) pelvic model with anterior column and posterior hemi-transverse acetabular fractures was created. Three common fixation systems were used to fix the posterior wall acetabular fractures: 1. Anterior column plate combined with posterior column screws (group I), 2. Anterior column plate combined with quadrilateral area screws (group II) and 3. Double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 25 publications
4
27
0
Order By: Relevance
“…For custom pelvic implants, fixation design is important, considering that the fixation secures the pelvic implants to the remaining bones, and should bear substantial loads as well [9]. A double column plating or a single column plating combined with lag screws has been commonly utilized to fix pelvic bones.…”
Section: Introductionmentioning
confidence: 99%
“…For custom pelvic implants, fixation design is important, considering that the fixation secures the pelvic implants to the remaining bones, and should bear substantial loads as well [9]. A double column plating or a single column plating combined with lag screws has been commonly utilized to fix pelvic bones.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous research, we reported a new fixation technique called DAPSQ for complex acetabular fractures with quadrilateral plate involvement and obtained satisfactory clinical results 4 . Biomechanical studies have investigated the biomechanical stability of DAPSQ devices [19][20] . As described earlier, the DAPSQ plate was a simple and ingenious design based on the traditional reconstruction plate and specially shaped, just like a "curl" or "Moebius strip."…”
Section: Key Surgical Technology Of Double-column Acetabular Fracturesmentioning
confidence: 99%
“…A number of studies have focused on the biomechanical consequences of acetabular fracture [28][29][30][31][32]. These studies can be divided into those focusing on.…”
Section: Biomechanical Consequences Of Acetabular Fracturementioning
confidence: 99%
“…Several studies have focused on the alteration of contact area and stresses in the joint as a result of the fracture [28][29][30][31][32]. All fracture patterns showed a change from a uniform contact pattern to one of increased contact area and peak pressures in the superior acetabulum.…”
Section: Intra-articular Contact Characteristicsmentioning
confidence: 99%